EVALUATION OF THE EFFECT OF THE PECTINS OF THE DATES (PHOENIX DACTYLIFERA L) ON THE BIOCHEMICAL INDICATORS OF LEAD POISONING IN MALE WISTAR RATS - Sadi, N.; Ouldali, O.; Bekara, A.; Aoues, A. (University of Eloued جامعة الوادي, 2017)
This study is conducted to examine the effect of the oral administration of pectin of dates on perturbation of the biochemical parameters induced by lead. Male rats were exposed to lead acetate at 350mg/Kg for one month, after this period, rats treated during one month with the pectin of date at 3%. Rats were sacrificed, the blood and urine are collected for the biochemical assays: glucose, total protein, phosphatase acide (PAC), alkaline phosphatase (PAL), aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine, urea and uric acid. The results showed that the exposure to lead has induced a disturbance in the biochemical parameters. Thus, the treatment by the pectin of dates reduced the high concentration of these parameters. Our results show that the pectins of dates may have a corrective effect on the biochemical disturbances induced by the lead.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Phoenix Dactylifera; Pectin; Lead; Biochemical parameters